Analisis Peran Guru dalam Pembudayaan Literasi Sains pada Siswa Kelas 4 Sekolah Dasar - Aminah Nurhanifah; Ratnasari Diah Utami (Jurnal Elementaria Edukasia, 2023)
The lack of literacy gives birth to apathetic students in looking at a problem. The objectives of this study are: 1) the role of teachers in cultivating science literacy of grade IV students, 2) factors that become obstacles in implementing science literacy culture in elementary schools, and 3) how teachers solve obstacles to cultivating science literacy of grade IV students. This study uses qualitative methodology and combines literature studies with field research techniques. The literature study is to collect data through primary and secondary data sources. Data collection through observation, interviews, and documentation of grade IV students who are the focus of research. Interviews, observations, and documentation were used as data collection strategies. Data reduction, data presentation, and making conclusions are the three stages of data analysis used in this study. The validity of the data in this study used a triangulation approach. The results showed that: 1) The role of teachers in cultivating science literacy of grade IV students is one of learning using direct practice; 2) One of the inhibiting factors in applying science literacy culture is only focused on memorizing material without understanding in detail the science; 3) The solution is to create study groups to complement each other's shortcomings. It can be concluded that the role of teachers is important in cultivating science literacy for grade IV students.